Bahasa Inggris - Wati, Tiara Cantika; Tawami, Tatan (Fakultas Ilmu Budaya, Universitas Komputer Indonesia, 2024)
This research aims to analyze the psychological structure of the main character, Lily Bloom, in the novel It Ends with Us by Colleen Hoover. This research discovered the character structures of the Id, Ego, and Superego in the main character, which produced the most dominant psychological structure based on Sigmund Freud's theory. The researcher used a qualitative descriptive method based on the novel's dialogue and English story descriptions. It Ends With Us was the primary data source in this research. This research identifies ten results that show that the id dominates Lily Bloom's character. Lily Bloom shows a psychological structure resulting from her past trauma, trauma caused by violence perpetrated by her father and husband. Each of these five results identified that Lily Bloom is dominated by Id. Keywords: Psychological structure, characters, Psychoanalysis, Id, Ego, Superego